Hyperglycemia predicts persistently lower muscle strength with aging - Kalyani, Rita Rastogi; Metter, E Jeffrey; Egan, Josephine; Golden, Sherita H; Ferrucci, Luigi (Diabetes care, 2015)
Persons with diabetes have accelerated muscle loss compared with their counterparts. The relationship of hyperglycemia per se to declines in muscle function has not been explored yet has implications for developing appropriate intervention strategies to prevent muscle loss. We examined 984 participants aged 25-96 years in the Baltimore Longitudinal Study of Aging (2003-2011) with HbA1c, knee extensor strength (isokinetic dynamometer), and lean body mass (DEXA) measured at baseline. Participants had repeated measurements up to 7.5 years later. Muscle quality was defined as knee extensor strength/leg lean mass. Participants were categorized by HbA1c quartile (<5.5, 5.5-5.79, 5.8-6.09, and ≥6.1% or <37, 37-40, 40-43, and ≥43 mmol/mol). Mixed-effects regression models were used to examine the regression of muscle outcomes on HbA1c. Muscle strength and quality were significantly lower across HbA1c quartiles (both P < 0.001), without differences in muscle mass at baseline. Comparing highest versus lowest HbA1c quartiles and adjusting for age, race, sex, weight, and height, strength was significantly lower (-4.70 ± 2.30 N · m; P value trend = 0.02) and results were unchanged after adjustment for physical activity (P value trend = 0.045) but of borderline significance after additional adjustment for peripheral neuropathy (P value trend = 0.05). Adjusting for demographics, muscle quality was significantly lower (-0.32 ± 0.15 N · m/kg; P value trend = 0.02) in the highest versus lowest HbA1c quartiles, but differences were attenuated after adjusting for weight and height (-0.25 ± 0.15 N · m/kg; P value trend = 0.07). Muscle mass measures were similar across HbA1c quartiles. Hyperglycemia is associated with persistently lower muscle strength with aging, but this effect may be mediated, at least in part, by peripheral neuropathy. Future studies should explore if better glycemic control can preserve muscle function in diabetes.